Basic Points to Consider for Cell Storage under the Act on the Safety of Regenerative Medicine in Japan - Yuki Uno; Kazuaki Nakamura; Morikuni Tobita; Manabu Mizutani; Masatoki Watanabe; Kosuke Kawai; Masahiro Kino-oka (Regenerative Therapy, 2025)
Regenerative medicine is an emerging field of medical treatment characterized by numerous uncertainties, necessitating regulatory frameworks that ensure both patient safety and timely clinical application. Among the three legislative measures established in Japan to facilitate the safety and efficient implementation of regenerative medicine, the Act on the Safety of Regenerative Medicine (RM Safety Act) governs regenerative medicine and cell therapies (RMTs) that utilize processed cells without manufacturing and marketing authorization. These therapies are conducted either as non-commercial clinical trials or as out-of-pocket therapies at the discretion of medical practitioners. More than a decade has passed since the enactment of the RM Safety Act, during which various aspects of RMTs have been clarified. The Evaluation Committee on Regenerative Medicine, Health Sciences Council, published the Summary of the Review of the Act on the Safety of Regenerative Medicine, 5 Years After Its Enforcement, which highlighted key challenges, including the lack of specific regulatory provisions for the storage of cells used in RMTs. In response, the Japanese Society for Regenerative Medicine developed the Basic Points to Consider for Cell Storage under the Act on the Safety of Regenerative Medicine, which outlines guidelines for practitioners intending to store human-derived, specified processed cells and/or their raw materials in a frozen state, as well as for institutions that provides cell storage. This review summarizes the current status and challenges of the RM Safety Act from the perspective of cell storage and provides an overview of the Basic Points to Consider for Cell Storage under the Act on the Safety of Regenerative Medicine and its role as an educational resource.